A coupled agent-based model to analyse human-drought feedbacks for agropastoralists in dryland regions - Streefkerk, Ileen N.; de Bruijn, Jens; Haer, Toon; Van Loon, Anne F.; Quichimbo, Edisson A.; Wens, Marthe; Hassaballah, Khalid; Aerts, Jeroen C. J. H. (Frontiers in Water, 2023)
Drought is a persistent hazard that impacts the environment, people’s livelihoods, access to education and food security. Adaptation choices made by people can influence the propagation of this drought hazard. However, few drought models incorporate adaptive behaviour and feedbacks between adaptations and drought. In this research, we present a dynamic drought adaptation modelling framework, ADOPT-AP, which combines socio-hydrological and agent-based modelling approaches. This approach is applied to agropastoral communities in dryland regions in Kenya. We couple the spatially explicit hydrological Dryland Water Partitioning (DRYP) model with a behavioural model capable of simulating different bounded rational behavioural theories (ADOPT). The results demonstrate that agropastoralists respond differently to drought due to differences in (perceptions of) their hydrological environment. Downstream communities are impacted more heavily and implement more short-term adaptation measures than upstream communities in the same catchment. Additional drivers of drought adaptation concern socio-economic factors such as wealth and distance to wells. We show that the uptake of drought adaptation influences soil moisture (positively through irrigation) and groundwater (negatively through abstraction) and, thus, the drought propagation through the hydrological cycle.